Lipopolysaccharide-binding protein cannot independently predict type 2 diabetes mellitus: A nested case-control study - Zhou, Huang; Hu, Jinbo; Zhu, Qibo; Yang, Shumin; Zhang, Yi; Gao, Rufei; Liu, Lulu; Wang, Yue; Zhen, Qianna; Lv, Qiong; Li, Qifu (Journal of diabetes, 2016)
Background Cross‐sectional studies have reported a close association between serum lipopolysaccharide‐binding protein (LBP) and many metabolic disorders. However, no longitudinal study has explored the relationship between LBP and type 2 diabetes mellitus (T2DM). The aim of the present study was to investigate the association between serum LBP levels and the risk of developing T2DM. Methods A 5‐year nested case‐control study of 3510 individuals was performed as part of the Environment, Inflammation and Metabolic Diseases Study (EIMDS). Clinical data were collected at baseline. Serum levels of LBP and other biochemical factors, such as insulin and high‐sensitivity C‐reactive protein, were detected 5 years later. Subjects were diagnosed as having T2DM on the basis of results of an oral glucose tolerance test (OGTT) and 1998 World Health Organization criteria. Controls were randomly selected to match cases according to age, gender, and body mass index (BMI) in a 1:1 ratio. Odds ratios (OR) for T2DM were calculated using conditional logistic regression analysis. Results Over a 5‐year follow‐up period, 255 subjects developed T2DM. There was no significant difference in serum LBP levels between the T2DM and control groups at baseline (19.78 ± 6.40 versus 20.53 ± 6.99 μg/mL; P = 0.207). Subjects were divided into three groups based on tertiles of LBP concentrations (n = 170 in each group; T1 = 1.31–17.16 μg/mL LBP; T2 = 17.21–22.37 μg/mL LBP; T3 = 22.49–40.08 μg/mL LBP). There was no significant association between the risk of developing T2DM and any of the LBP tertiles in either a simple model or after adjusting for general status and biochemical factors. Conclusion After matching for gender, age, and BMI, LBP does not improve prediction of the development of T2DM independently. 摘要 背景 既往的横断面研究提示脂多糖结合蛋白(lipopolysaccharide‐binding protein,LBP)与多种代谢紊乱密切相关,然而尚缺乏纵向研究来揭示LBP与2型糖尿病之间的关系。因此,本研究的目的在于探索血清LBP水平与2型糖尿病的发病风险是否相关。 方法 本研究是环境、炎症及代谢性疾病研究(Environment, Inflammation and Metabolic Diseases Study,EIMD)中的一部分。采用巢式病例对照研究的方法,于基线收集临床资料并追踪随访5年,测定基线时血清LBP、超敏C反应蛋白(high sensitive C reactive protein,hs‐CRP)及其他生物学指标水平。分别在基线和随访期间行口服75 g葡萄糖耐量试验(oral glucose tolerance test,OGTT),并根据1998年世界卫生组织(World Health Organization, WHO)标准诊断糖尿病。按1:1选取与新诊断2型糖尿病患者的性别、年龄、体质指数(body mass index,BMI)相匹配的糖耐量正常者作为对照组。采用条件logistic回归分析LBP对2型糖尿病发病风险的影响。 结果 在5年随访期间,2541名受试者中新诊断2型糖尿病为255例,2型糖尿病组与对照组基线血清LBP水平无统计学差异(19.78 ± 6.40 vs. 20.53 ± 6.99 µg/mL,P = 0.207]。根据血清LBP三分位水平将所有研究对象分为三组(每组170人;T1 = 1.31‐17.16 µg/mL LBP;T2 = 17.21‐22.37 µg/mL LBP;T3 = 22.49‐40.08 µg/mL LBP),结果提示随着LBP分位增高,血糖及2型糖尿病发生人数无明显变化。无论是未校正或是校正多因素后,2型糖尿病的发病风险均不随血清LBP水平升高而增加。 结论 在性别、年龄、BMI相匹配的情况下,血清LBP水平升高未增加2型糖尿病的发病风险。